P658Adaptation to continuous normobaric hypoxia affects mitochondrial enzymes in spontaneously hypertensive rat hearts. (15th July 2014) - Kalous, M; Weissova, R; Drahota, Z; Brabcova, I; Zurmanova, J; Novakova, O; Pravenec, M; Kolar, F; Neckar, J
Abstract: Purpose: Adaptation to continuous normobaric hypoxia (CNH) increases cardiac ischemic tolerance. The protective role of cardiac mitochondria has been suggested in CNH. The present study investigated the effects of CNH on the expression and activity of selected mitochondrial proteins in spontaneously hypertensive rats (SHR), and in a novel conplastic strain SHR-mtBN. This strain is characterized with a selective replacement of the mitochondrial genome of SHR with more ischemic tolerant Brown Norway (BN) strain. Methods: Rats were kept 21 days at CNH (inspired O2 fraction 0.1). Left ventricular homogenate was used to assess the enzyme activity of malate dehydrogenase (MDH), citrate synthase (CS), NADH-cytochrome c oxidoreductase, succinate-cytochrome c oxidoreductase and cytochrome oxidase (COX). Protein and mRNA expression of the subunits of oxidative phosphorylation complexes (CI - Ndufa9, CII - Sdha, CIII- Uqcrc2, CIV - COX-4 and MTCO1, CV - Atp5a1) were evaluated using immunoblotting and RT-PCR. Results: Normoxic SHR-mtBN has by 14% lower amount of complex IV subunit MTCO1 (encoded by BN mitochondrial genome) compared to SHR. Adaptation to CNH resulted in raised content of complex IV subunits by 17% in both strains compared to normoxic controls. In addition, MDH activity decreased by 23% only in hypoxic SHR. These changes resulted in significant differences between SHR and SHR-mtBN after adaptation to CNH. As compared both hypoxic strains, SHR-mtBN demonstrated higher MDH activity and protein amount of Ndufa9 subunit of complex I, whereas the protein content of COX-4 and MTCO1 subunits of complex IV were lower compared to SHR. The expression on the mRNA level was decreased for CS (by 45%) as well as for cytochrome oxidase isoforms subunits COX 4.1 and COX 4.2 (by 22% and 23%, respectively) in the conplastic strain adapted to CNH compared to normoxic control. However, in the CNH adapted SHR strain, the decrease in mRNA level was found for COX 4.1 only (by 28%). Conclusions: Adaptation to CNH affected myocardial expression and activity of mitochondrial proteins in hypertensive strains, and replacement of the mitochondrial genome of SHR with BN modified the response to CNH. This work was supported by the Czech Science Foundation grant no. 13-10267S